Implementing the Nursing Process in Improving Nurse Performance Literature Review - Suci, Amin; Dioso, Regidor III (International Journal of Health Sciences, 2024)
Introduction: The nursing process is a scientific method used in providing professional nursing care. Nurses in dealing with clients with all kinds of cases, and serving clients at all ages must also use the nursing process. This study aims to understand the application of the nursing process in improving nurse performance because the nursing process includes five stages that are consistent with the development of the nursing profession. Material and Methods: This study uses literature review based on textbooks, reference books, ebook journals (last 5 years) by analyzing, exploring, and free study. Results: The application of the nursing process in providing nursing care to clients is to solve problems. The nursing process can also be used to develop an intervention that aims to change a situation that is more conducive in helping to accelerate the resolution of very complex client problems. Improvement of nursing process will be followed by improvement of nurse performance. In this case, nurses not only implement nursing care but nurses can also develop their abilities so that patients are satisfied with the services provided through the nursing process.Conclusion: The implementation of optimal nursing processes in hospitals will support the improvement of nurse performance as a health service. The quality of health services must start from patient needs and end with patient satisfaction and positive perceptions of service quality.